(untitled) (Texas Journal of Medical Science, 2023)
In the literature, there are practically no results of studies aimed at studying the clinical picture of ankylosing spondylitis (AS) in the actual practice of rheumatologists in Uzbekistan. Meanwhile, such studies can provide information not only about the epidemiological aspects of the disease, but also about the diversity of its clinical picture, medical and social significance, and allow assessing the effectiveness of therapy and planning the system of medical costs for the future